Effect of fiber hybridzation of the behaviour of oil palm shell concrete slab - Nursyazwani, Mat Lazim (2015)
Oil palm shell (OPS) is considered as a waste material originating from the oil palm industry. On the other hand, steel fibre can act as an unconventional material to reduce the sensitivity of OPS concrete. Hybridization of fibre leads to improvements on the mechanical and ductility characteristics of the concrete. In this research, the effect of steel hybrid fibre on the compressive strength and ultimate shear failure concrete slab were studied. Cube compressive strength and combined bending and shear tests for the slab were conducted. OPS that were used are from Kilang Panching while steel fibres are from a factory at Klang. In this study, aspect ratio and volume fraction were emphasized in selecting the most suitable type of steel fibre. The results on the cube compressive strengths shows range of 12.4 MPa – 14.9 MPa, 10.2 MPa – 12.7 MPa and 12.0 MPa – 13.7 MPa for B1, B2 and B3 cubes, respectively. The values were slightly lower than the design concrete strength of 20 MPa. On the other hand, the ultimate shear failure gives range of 36.0 kN – 60.5 kN, 37 kN – 46 kN, 38 kN – 47 kN for B1, B2 and B3 slabs, respectively. As a conclusion, slabs with longest length of steel fibre, SF60 shown better structural performance compared with other length. In terms of hybridization effect, it shows none improvement to the structural slab.